Alteration of Gene Expression After Entecavir and Pegylated Interferon Therapy in HBV-Infected Chimeric Mouse Liver - Huarui Bao; Serami Murakami; Masataka Tsuge; Takuro Uchida; Shinsuke Uchikawa; Hatsue Fujino; Atsushi Ono; Eisuke Murakami; Tomokazu Kawaoka; Daiki Miki; Clair Nelson Hayes; Shiro Oka (Viruses)
Cross-sectional analyses using liver tissue from chronic hepatitis B patients make it difficult to exclude the influence of host immune responses. In this study, we performed next-generation sequencing using the livers of hepatitis B virus (HBV)-infected uPA/SCID mice with humanized livers before and after antiviral therapy (AVT) with entecavir and pegylated interferon, and then performed a comparative transcriptome analysis of gene expression alteration. After HBV infection, the expression of genes involved in multiple pathways was significantly altered in the HBV-infected livers. After AVT, the levels of 37 out of 89 genes downregulated by HBV infection were restored, and 54 of 157 genes upregulated by HBV infection were suppressed. Interestingly, genes associated with hypoxia and KRAS signaling were included among the 54 genes upregulated by HBV infection and downregulated by AVT. Several genes associated with cell growth or carcinogenesis via hypoxia and KRAS signaling were significantly downregulated by AVT, with a potential application for the suppression of hepato-carcinogenesis.